Congenital Choanal Atresia A Case Report - Begum, Tahmina; Shamsad, Iffat Ara; Anwar, Sayeeda; Afroza, Syeda (Bangladesh Journal of Child Health, 2010)
DOI: 10.3329/bjch.v30i1.6190 Bangladesh J Child Health 2005; Vol 29 (3): 107-110